2012
DOI: 10.1111/j.1468-0343.2012.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Special Interest Group Formation in the United States: Do Special Interest Groups Mirror the Success of their Spatial Neighbors?

Abstract: Special interest groups exert a great deal of influence over political outcomes in the United States. Understanding the determining factors for the formation of special interest groups is important. However, the literature has excluded the role of spatial neighbors. This article employs spatial econometric techniques to discriminately analyze the factors determining the number of special interest groups in a state. While geographic location is not a factor, gross state product, state general expenditures, unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As discussed, the empirical evidence on how lnGOVSPEND affects SIGs' activities is mixed, inconclusive, and contradictory. If increasing lnGOVSPEND leads to rising lnSIGS (the rent‐seeking view), then the coefficient on lnGOVSPEND is expected to be positive and statistically significant (δ3>0 ${\delta }_{3}\gt 0$); however, if fewer interest groups form as government spending increases (e.g., Randolph & Tasto, 2012) then the coefficient on lnGOVSPEND is expected to be negative and statistically significant (δ3<0 ${\delta }_{3}\lt 0$); or not statistically significant if lnGOVSPEND does not affect the formation of SIGs (e.g., Mueller & Murrell, 1986). As noted, how income inequality affects SIGs' activity has received little attention in the empirical literature and lacks theoretical guidance.…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed, the empirical evidence on how lnGOVSPEND affects SIGs' activities is mixed, inconclusive, and contradictory. If increasing lnGOVSPEND leads to rising lnSIGS (the rent‐seeking view), then the coefficient on lnGOVSPEND is expected to be positive and statistically significant (δ3>0 ${\delta }_{3}\gt 0$); however, if fewer interest groups form as government spending increases (e.g., Randolph & Tasto, 2012) then the coefficient on lnGOVSPEND is expected to be negative and statistically significant (δ3<0 ${\delta }_{3}\lt 0$); or not statistically significant if lnGOVSPEND does not affect the formation of SIGs (e.g., Mueller & Murrell, 1986). As noted, how income inequality affects SIGs' activity has received little attention in the empirical literature and lacks theoretical guidance.…”
Section: Methodology and Datamentioning
confidence: 99%
“…As already indicated, the findings of Sobel and Clark (2016) indicate that government spending significantly and positively affects SIGs' activities, thereby supporting the TRSB. However, this finding is contradicted by Randolph and Tasto (2012), who examined the factors determining the formation of SIGs in the US states over time, the first to use spatial dependency models in such analysis. Based on 1990Based on , 1997Based on , 1998Based on , and 1999 state data and GS2SLS-GMM regressions, using the number of registered interest group organizations by the state as the dependent variable, and controlling for factors such as gross state product, voter initiatives, divided governance, the population over 65 years old, and the quality of state institutions, found that government spending as a percentage of gross state product is negative and statistically significant in the various spatial models, indicating that as government spending increases fewer interest groups will form.…”
Section: The Links Between Sigs and Govspend On Side C Of The Trianglementioning
confidence: 98%
See 1 more Smart Citation
“…The studies in the literature generally determine that pressure and interest groups have a positive effect on the public sector size (McCormick & Tollison, 1981;Mueller & Murrell, 1986;Fiorino & Ricciuti, 2009;Yamamura, 2012). The relationship among variables in the studies like the ones of Bacot and Dawes (1986), Gray and Lowery (1988), Newmark and Witko (2007), Randolph and Tasto (2012), and Holyoke and Cummins (2019), determine that interest groups have a positive effect on public expenditures in the USA for the period 2006-2015. Similarly, Randolph and Tasto (2012) conducted a spatial analysis for the states within the USA and reached the conclusion that public expenditures are crucial in the formation of special interest groups through states.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship among variables in the studies like the ones of Bacot and Dawes (1986), Gray and Lowery (1988), Newmark and Witko (2007), Randolph and Tasto (2012), and Holyoke and Cummins (2019), determine that interest groups have a positive effect on public expenditures in the USA for the period 2006-2015. Similarly, Randolph and Tasto (2012) conducted a spatial analysis for the states within the USA and reached the conclusion that public expenditures are crucial in the formation of special interest groups through states. From this perspective, the effects of interest groups on public expenditures in Turkey have been examined.…”
Section: Introductionmentioning
confidence: 99%